Pengaruh faktor personaliti, penghargaan kendiri dan perjawatan kepimpinan terhadap kepimpinan kendiri dalam kalangan pelajar di negeri Johor - Nasrul Hakim,; Fatimah Wati Halim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Self-leadership has received limited attention particularly in the local education field. According to Manz (1986), self-leadership is a process whereby individuals influence and lead themselves towards their desired goals, which is crucial for the personal development of high school students towards a proper mindset approaching adulthood. This study aims to study the influence of personality, self-esteem, and leadership roles towards self-leadership. Moreover, this research seeks to study the differences in self-leadership, personality, and self-esteem according to leadership roles. This study involved 461 upper secondary students across Johor, utilizing a cross-sectional quantitative research design with purposive sampling technique. Multiple regression analysis revealed that agentic personality traits which are openness and extraversion, along with leadership roles, significantly predicted self-leadership. Conversely, self-esteem had no significant influence on self-leadership. T-test analysis indicated that student leaders, had significantly higher means in self-leadership, self-esteem, openness, conscientiousness, extraversion, and agreeableness compared to students without leadership roles, namely non-leader students. Furthermore, non-leader students showed significantly higher mean in neuroticism compared to student leaders. This study underscores the significance of fostering self-leadership in students by emphasizing the development of openness and extraversion traits through leadership modules, trainings, hands-on program management experiences, and early exposure to leadership roles in school.